Calcium Addition, pH, and High Hydrostatic Pressure Effects on Soybean Protein Isolates—Part 1: Colloidal Stability Improvement - Manassero, Carlos Alberto; David-Briand, Elisabeth; Vaudagna, Sergio Ramon; Anton, Marc; Speroni, Francisco (2018)
Calcium addition to soybean protein dispersions increases nutritional value but harms functional properties, such as protein solubility and colloidal stability. The high hydrostatic pressure (HHP) treatment can reverse those effects. The aims of this work were to evaluate the influence of pH and protein and calcium concentration on HHP solubilizing/stabilizing effect and to characterize the physicochemical properties of HHP-stabilized species. Proteins without calcium addition were stabilized by HHP at both pHs. However, calcium-added proteins behaved differentially: at pH 5.9, the effect was verified only at low protein concentration, whereas at pH 7.0, the effect was verified under both assayed protein concentrations (5 and 10 g L−1) and with a higher magnitude in calcium-added samples. Moreover, at pH 7.0, the effect was independent of the order of calcium addition and HHP treatment, whereas at pH 5.9, the effect was smaller when calcium was added after HHP treatment. At both pHs, the solubilizing/stabilizing effect of HHP on soybean proteins seemed to be largely dependent on the decrease in the size of protein species. The smaller the size, the greater the amount of protein that remained in dispersion after intense centrifugation (10,000g, 20 min, 4 °C). Although the effect of HHP consisted, at least in part, of stabilizing insoluble protein, turbidity decreased in all samples after HHP treatment. By combining different levels of pH, calcium, and protein concentrations, translucent or turbid colloidal-stable dispersions can be obtained by HHP treatment.